GAMBARAN PENGETAHUAN DAN SIKAP PASIEN TB PARU TERHADAP UPAYA PENGENDALIAN TB DI PUSKESMAS SIDOMULYO KOTA PEKANBARU - Refica Dewita Sarmen; Surya Hajar FD; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2017)
ABSTRACTTuberculosis is an infectious disease caused by Mycobacterium tuberculosis, which remains a global health threat. In Indonesia pulmonary TB is still a serious health problem with incidence rates are quite high. Pulmonary TB can be contained and prevented if people have knowledge and a good attitude so as to produce the appropriate control measures. The purpose of this study is to describe the knowledge and attitudes of TB patients in order to control efforts of TB in Puskesmas Sidomulyo Pekanbaru.The study was conducted in June 2016. This is a descriptive obeservational study with crosecctional approach. The instrument used was a questionnaire about knowledge, attitudes, and actions. The number of respondents is 31 patients of TB who were registered on the form of TB 06 in Puskesmas Sidomulyo Kota Pekanbaru and it has meet inclusion criteria of study. Results showed that sex characteristic of patients were predominantly male as many as 23 people (74,2%) and the most productive among patients aged 18-40 years as many as 20 people (64,5%). Characteristics by education level showed as many as 19 patients (61,3 %) was high school graduates and 90,3% had undergone treatment > 2 months. The result showed that respondents who have a quite good level of knowledge about tuberculosis as many as 12 people (38,7 %). Based on the attitudes showed that a positive attitude as many as 27 people (87%) and quite good level of actions as many as 4 people (13%).Keyword: Attitude,Action, Knowledge,Tuberculosis